The silenced voices of desire in the novel Eating Wasps - et. al., Hema. R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present paper analyses the women characters Urvashi, Sreelakhmi, Brinda and Najma in the novel Eating Wasps. The protagonist is the ghost of Sreelakshmi and she takes the readers through the lives of other women in the novel. Anita Nair portrays the confined lives of women even in the modern society. She portrays a society that considers women’s desires as a sin. Gender roles are deeply engrained in the minds of both men and women in a patriarchal society. The family and society consider women’s desires as unnatural. They are silenced and are forced to live a life they despise. The paper discusses the shame and guilt faced by the women in the novel and the gender discrepancies in the society.